Integration of Nationalistic and Religious Values in Islamic Education: Study in Integrated Islamic School - Akhsanul Fuadi; Suyatno Suyatno (RIRAI Publisher, 2020)
The education that integrates nationalistic and religious values expected to transform the student to be good citizens and God’ obedient servants. This research aims to explore two purposes: first, what is the purpose based on the integration of nationalistic and religious in learning in Integrated Islamic School; second, how is the teacher’s strategy in Integrated Islamic School in integrating nationalistic and religious in learning conducted. This research is qualitative research with case study approach. The data was taken from the interview of seven teachers in Integrated Islamic School of Yogyakarta Region from primary school to secondary school and documentation. The data collected was analyzed by interactively inductive data analysis technique of Miles and Huberman model consisting of data collection, data reduction, data display, and conclusion withdrawal. The finding of this research showed that; first, the integration of nationalistic and religious values was conducted based on the ideal Indonesian human concept that is the obedient human of Indonesian towards the state in which the main indicator is nationalism also the obedient human of Indonesian towards God in which the main indicator is religious soul. Second, the integration of nationalistic and religious values conducted through three main strategies, namely; integration in curriculum, co-curriculum, and extraculliculer; internalization of nationalistic and religious values; and habitual activity of nationalistic and religious values in the school culture. The finding of this research can be used as reference for teachers in implementing the strategy in integrating nationalistic and religious values to students.